Scaling patterns of human diseases and population size in Colombia. (July 2022) - Feged-Rivadeneira, Alejandro; Andrade-Rivas, Federico; González-Casabianca, Felipe; Escobedo, Francisco J.
Highlights: Studying emergent properties of complex spatial interactions is challenging. Scale free analysis can be used to overcome data biases. Disease dynamics were described by power-laws. Our analysis can be used to inform public policy. Abstract: Colombia has had one of the largest numbers of internally displaced populations in the world and in 2016 entered a period of post-conflict. These socio-ecological and geopolitical processes and trends have increased the migration of people towards cities and accordingly are affecting the distribution and occurrence of tropical diseases in its urban and peri-urban areas. Studies have suggested that anthropogenic phenomena such as urbanization scale according to the size of human populations regardless of cultural context. But, other studies show that health epidemics such as malarial and human immunodeficiency virus infections, follow a scale-free distribution in terms of urban population size and density. Here, we explore these relationships and dynamics in a tropical context using statistical analyses and available geospatial data to identify the scale relationships between urban growth processes and disease transmission in Colombia. Our results show that the dynamics of rural populations and certain diseases were characterized by power-laws that are indeed observed in urbanization studies. However, as opposed to these other studies, we found that malaria presented a higher intensity of infection in human settlements with less than 50, 000 individuals and in particular for ethnic, indigenous populations. Results indicate that disease and urbanization relationships in Colombia do indeed follow scales; findings that differ from previous epidemiological studies such as those for malarial infection. Additionally, we identified trends showing that malarial infections become endemic in peri-urban areas. This approach using few, but robust and readily available, data is key for managing public health issues and understanding the spatial distribution of environmental impacts in the urbanizing tropics.